Analisis Penerapan Bagi Hasil Dan Tingkat Religiusitas Terhadap Minat Masyarakat Menabung Pada Tabungan Mudharabah Di Bank Syariah Purwakarta - Putra, Aldi Kurnia; Suartini, Sri (Jurnal Ilmiah Wahana Pendidikan, 2023)
PT.Bank Syariah Indonesia Tbk is one of the Islamic banks in Purwakarta that implements a profit-sharing system for its customers. The purpose of this study is to find out whether the application of profit-sharing and the level of religiosity can influence people's interest in saving or whether is it more dominantly influenced by other factors. The method used in this research is quantitative, namely, research that emphasizes the amount of data collected through respondents' answers from questionnaires and then processed using SPSS software version 25. And also in helping to complete this research interview methods and direct observation are needed on the spot. From the data that has been collected, the results show that the majority of respondents stated that the application of profit sharing and the level of religiosity affected their interest in saving in mudharabah savings at Islamic banks in Purwakarta.